Determination of model characteristics of technical and tactical indicators of highly qualified female swimmers, who specialize on the distance of 50 meters by different strokes - Olga Pylypko; Alina Pylypko; Alina Shynkarenko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to develop the model characteristics of technical and tactical indicators of highly qualified female swimmers, who specialize on the distance of 50 meters by different strokes. Material and methods: analysis of literary sources, timing, video filming, methods of mathematical statistics. The surveyed contingent consisted of participants of the final heats of the Swimming Championships and Cups of Ukraine at the distance of 50 meters by different strokes. The level of sports qualifications of the sportswomen corresponded to the titles of Master of Sports of Ukraine and Master of Sports of Ukraine of international class. Results: the influence of indicators of swimming speed, tempo and «step» of the cycle of rowing movements on the result of overcoming the distance of 50 meters by different strokes by highly qualified sportswomen investigated; the most significant parameters of the technical and tactical skill of highly qualified female swimmers depending on the swimming stroke determined and their model characteristics developed. Conclusions: the influence of the indicators of swimming speed, tempo and «step» of the cycle of rowing movements on the result of overcoming the distance of 50 meters by highly qualified sportswomen has characteristic features depending on the swimming stroke. The most significant technical and tactical parameters in front crawl swimming is the speed on the segments «15 m - 25 m» and «45 m - 50 m», the tempo of the rowing movements on the sections «35 m - 45 m» (R is -0,60, -0,72 and -0,72 respectively). In the backstroke swimming the result mainly depends on the fast swimming of the first 35 meters of the distance (R values ​​are in the range of -0,57 - -0,98), as well as the tempo values ​​on the segment «25 m - 35 m» (R = -0,50). Efficiency at the distance of 50 meters by breaststroke swimming is influenced by the speed indicators of overcoming the sections «emerging - 15 m», «25 m - 35 m» and «45 m - 50 m», the tempo of rowing movements on the segments «emerging - 15 m» and «15 m - 25 m», the ability to maintain a large «step» on the sections «15 m - 25 m» and «25 m - 35 m» (R at the level of values ​​-0,88, -0,56, -0,86, -0,55, -0,70, 0,79 and -0,69 respectively). The result in the butterfly stroke mostly depends on the fast passage the underwater area and the second half of the distance of 50 meters (R within 0,58 - 0,86). The tempo and «step» of the cycle of rowing movements closely correlate with the final result on the second half of the competitive distance (R values ​​vary from -0,70 to -0,97). Orientation on the developed model characteristics of the most significant indicators of technical and tactical skill of highly qualified female athletes, who have the different swimming specializations, will contribute to the improvement of training and competitive activity in modern swimming.